2021
DOI: 10.3389/fphys.2021.737474
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-5 Affects Endothelial Autophagy in Response to Early Hypoxia

Abstract: Hypoxic injury to cerebrovascular endothelial cells (ECs) after stroke leads to blood-brain barrier (BBB) dysfunction, which is commonly associated with disruptions of endothelial tight junctions (TJs) and increased permeability. Therefore, maintaining the structural integrity and proper function of the BBB is essential for the homeostasis and physiological function of the central nervous system (CNS). Our previous study revealed that autophagy functions on protecting the BBB by regulating the dynamics of Clau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…It is well known that two intracellular degradation pathways are responsible for the degradation of most proteins in eukaryotic cells, autophagy and UPS [18–20]. Meanwhile, our recent studies have also revealed bidirectional regulations of the dynamic of claudin‐5 and autophagic activation [21]. Based on these, we questioned the potential correlations between intracellular degradation of claudin‐5 and autophagy.…”
Section: Resultsmentioning
confidence: 98%
“…It is well known that two intracellular degradation pathways are responsible for the degradation of most proteins in eukaryotic cells, autophagy and UPS [18–20]. Meanwhile, our recent studies have also revealed bidirectional regulations of the dynamic of claudin‐5 and autophagic activation [21]. Based on these, we questioned the potential correlations between intracellular degradation of claudin‐5 and autophagy.…”
Section: Resultsmentioning
confidence: 98%
“…There are limited reports on the effects of CLDNs-mediated autophagy. It was reported that CLDN5 knockout decreased autophagy in endothelial cells after hypoxia induction [ 37 ]. Wu et al found that CLDN1 upregulation significantly increased autophagy flux in esophageal squamous carcinoma cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…MDCK-II transfectants expressing mammalian CLDN5 could strengthen the paracellular barrier [ 50 ]. Moreover, the loss of CLDN5 results in the leakage of the BBB in vivo and in vitro [ 19 , 51 ]. Here, although the transfections of zebrafish-specific cldn5a into in vitro cells were missing, we verified that mammalian CLDN5 is required for establishing both epithelial and endothelial barriers in multiple cell models, consistent with its canonical sealing functions reported (Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%